Intelligent Secure Trustable Things - Karner, Michael; Peltola, Johannes; Jerne, Michael; Kulas, Lukas; Priller, Peter (Studies in Computational Intelligence, 2024)
XIX, 441 p. 212 illus., 192 illus. in color.